Mistisme Jalan Menuju Cahaya Ilahi - Epo, Nobertus (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2021)
In pre-religious times, primitive humans were aware of the cosmic power that governed the contents of the universe and human destiny. They offer various rituals such as songs, dances, offerings, sacrifices and prayers to worship their god. In a new chapter after people received revelation they began to look for the meaning of life that what we get in this world is only temporary. The question of what will happen to our bodies after death provides room for new reflections on the existence of a realm where death exists. Until the era of the development of philosophy, people were increasingly looking for identity by using their minds. Some people begin to think that what is material is false, impermanent and just an illusion. Finally those who received the ban withdrew and began to concentrate on finding a path to the divine for the sake of living a holy life. Mystics have succeeded in expressing the presence of divine love pouring out in their bodies and even that which is divine in the form of our daily actions.